Breast milk preservation: thermal and non-thermal processes and their effect on microorganism inactivation and the content of bioactive and nutritional compounds - Núñez-Delgado, Alejandro; Mizrachi-Chávez, Victoria Margarita; Welti-Chanes, Jorge; Macher-Quintana, Samantha Thania; Chuck-Hernández, Cristina (Frontiers in Nutrition, 2024)
Human Breast Milk (HBM) is widely acknowledged as the best nutritional source for neonates. Data indicates that 83.2% of infants in the United States receive breast milk at birth, slightly reducing to 78.6% at one month in 2019. Despite these encouraging early figures, exclusive breastfeeding rates sharply declined, dropping to 24.9% by six months. This decline is particularly pronounced when direct breastfeeding is challenging, such as in Neonatal Intensive Care Units (NICU) and for working mothers. Given this, it is vital to explore alternative breast milk preservation methods. Technologies like Holder Pasteurization (HoP), High-Temperature Short-Time Pasteurization (HTST), High-Pressure Processing (HPP), UV radiation (UV), and Electric Pulses (PEF) have been introduced to conserve HBM. This review aims to enhance the understanding of preservation techniques for HBM, supporting the practice of extended exclusive breastfeeding. It explicitly addresses microbial concerns, focusing on critical pathogens like Staphylococcus aureus, Enterococcus, Escherichia coli, Listeria monocytogenes, and Cytomegalovirus, and explores how various preservation methods can mitigate these risks. Additionally, the review highlights the importance of retaining the functional elements of HBM, particularly its immunological components such as antibodies and enzymes like lysozyme and Bile Salt Stimulated Lipase (BSSL). The goal is to provide a comprehensive overview of the current state of HBM treatment, critically assess existing practices, identify areas needing improvement, and advocate for extended exclusive breastfeeding due to its vital role in ensuring optimal nutrition and overall health in infants.